Identification and characterization of murine adipose tissue-derived somatic stem cells of Shenque (CV8) acupoint. Issue 22 (20th November 2021) - Hao, Yu-Hui; Liu, Zhi-Zhen; Zhao, Hong; Wang, Lei; Khan, Ajab; Mu, Jian-Bin; Wang, Yu-Fei; Yang, Li-Hong; Zhou, Ran; Xie, Jun
Abstract: Background: Shenque (CV8) acupoint is located on the navel and has been therapeutically used for more than 2000 years in Traditional Chinese Medicine (TCM). However, clinical research on the underlying therapeutic molecular mechanisms of the CV8 acupoint lags far behind. This study aimed to study the mechanisms of umbilical acupoint therapy by using stem cells. Methods: The morphological characteristics of CV8 acupoint were detected under a stereomicroscope using hematoxylin and eosin (H&E) staining. Oil Red, Masson, and immunohistochemical staining on multi-layered slices were used to identify the type of cells at the CV8 acupoint. Cell proliferation was measured by a cell counting kit-8 (CCK-8) method. Flow cytometry and immunohistochemistry were used for cell identification. Induced differentiation was used to compare the differentiation of cells derived from CV8 acupoint and non-acupoint somatic stem cells into other cell types, such as osteogenic, adipogenic, and neural stem cell-like cells. Results: Morphological observations showed that adipose tissues at the linea alba of the CV8 acupoint in mice had a mass-like distribution. Immunohistochemical staining confirmed the distribution of stem cell antigen-1 (Sca-1) positive cells in the multi-layered slices of CV8 acupoint tissues. Cells isolated from adipose tissues at the CV8 acupoint exhibited high expression of Sca-1 and CD44 and low expression of CD31 and CD34, and these cells possessed osteogenic, adipogenic, and neurogenic stem cell-like cell differentiation ability. The cell proliferation (day 4: 0.5138 ± 0.0111 vs . 0.4107 ± 0.0180, t  = 8.447, P  = 0.0011; day 5: 0.6890 ± 0.0070 vs . 0.5520 ± 0.0118, t  = 17.310, P  < 0.0001; day 6: 0.7320 ± 0.0090 vs . 0.6157 ± 0.0123, t  = 13.190, P  = 0.0002; and day 7: 0.7550 ± 0.0050 vs . 0.6313 ± 0.0051, t  = 42.560, P  < 0.0001), adipogenic ([9.224 ± 0.345]% vs. [3.933 ± 1.800]%, t  = 5.000, P =  0.0075), and neurogenic stem cell-like cell differentiation (diameter < 50 μm: 7.2000 ± 1.3040 vs . 2.6000 ± 0.5477, t  = 7.273, P  < 0.0001; diameter 50–100 μm: 2.6000 ± 0.5477 vs . 1.0000 ± 0.7071, t  = 4.000, P  = 0.0039; and diameter >100 μm: 2.6000 ± 0.5477 vs . 0.8000 ± 0.8367, t  = 4.025, P  = 0.0038) were significantly enhanced in somatic stem cells derived from the CV8 acupoint compared to somatic stem cells from the groin non-acupoint. However, cells possessed significantly weaker osteogenicity ([2.697 ± 0.627]% vs . [7.254 ± 0.958]%, t  = 6.893, P =  0.0023) in the CV8 acupoint group. Conclusions: Our study showed that CV8 acupoint was rich with adipose tissues that contained abundant somatic stem cells. The biological examination of somatic stem cells derived from the CV8 acupoint provided novel insights for future research on the mechanisms of umbilical therapy.